Penerapan Fungsi Retribusi Pasar Terhadap Layanan Infrastruktur Pedagang Pasar Tradisional di Desa Batetangngga (Perspertif Hukum Ekonomi Islam ) - Silvi Sustrihazlinda; Zainal Said; Rustam Magun Pikahulan (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2024)
The research investigates the traditional market levy in Batetangngga Village from an Islamic legal perspective. The aim of this study is to understand the function of market levies in providing trading facilities in the market. With two problem formulations: 1) how is the application of traditional market levies in Batetangngga Village, 2) How is the economic legal review of traditional market levies in Batetangngga Village. This research is qualitative using interview and observation techniques, and the data processing and analysis methods used in compiling this thesis are editing and verification. The results show that market levies in traditional markets come from the collection of business rental fees, cleanliness levies, electricity levies, and parking levies. These levies vary for each trader and are divided into several groups. Facilities available in Batetangngga Village traditional market include toilets, parking areas, and waste disposal facilities. The collection of levies in this traditional market does not comply with Islamic economic law because there are conditions not met by market officials, namely responsibility for repair and maintenance. However, market officials are not responsible for repairing facilities that have been paid for by traders. Taking away others' rights and causing harm to traders whose rights are taken is akin to stealing others' property. Taking someone else's rights is tantamount to committing injustice, a prohibition mentioned in the Qur'an and the Hadith of the Prophet.